Sustainability of electricity prices and the consequences for the Prague Stock Exchange - Florin Aliu; Simona Hašková; Petr Šuleř (Entrepreneurship and Sustainability Issues, 2022)
Sustainability of electricity prices hold an important part of the family budget, business operational costs, and vitality of the economy. Currently, multinational corporations are considered the main users of electricity and other energy recourses. For this purpose, we analyze the sustainability of electricity price and their impact equity stocks in the PX Index. The PX Index, which originates from Prague Stock Exchange is generally composed of firms in the financial and energy sector. This paper as well tries to predict the performance of these two variables in the 12 months ahead. The data cover the period from 1995 to 2022 standing on the monthly observations. The Vector Error Correction Model was used to detect the effect that electricity prices maintain on the PX Index. The estimated forecasts were conducted in the R program using Facebook Prophet and Auto ARIMA Model. The results indicate that non-sustainability of electricity prices negatively affect the equity stocks listed on the PX Index. Regarding predictions, the PX Index is expected to stay at almost the same levels while electricity prices increase. The results provide modest indications for investors, government, and regulators on the performance of these two indicators 12 periods ahead. Additionally, it is the first attempt to analyze the relationship between electricity prices and the equity markets since the liberalization of the Czech economy.